ORGANOCHLORINE PESTICIDES IN THE COASTAL SEDIMENT OF CITARUM ESTUARY, JAKARTA BAY: THE IMP ORTANT ROLE OF FINE FRACTION OF THE SEDIMENT AS THEIR AGENT TRANSPORT AND PROCESSES OF THEIR EARLY DIAGENESIS - T. Pratono; H. Razak; I. Gunawan (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2009)
DDT (1,1,1-Tricholor-2,2-bis(chlorophenil)ethane) and its two derivatives, DDD (1,1-Dicholor-2,2-bis(chlorophenil)ethane) and DDE (1,1-Tricholor-2,2-bis(chlorophenil)-ethylene) were identified in the coastal sediment of Citarum Estuary, Jakarta Bay.Eight stations of the sediment sampling were designed in order to obtain the changing of their concentration sadjacent to the estuary as possible input. Sediment samples were collected in the surface layer within a less than 5 cm depth. In addition to pesticides, texture of sediment and total organic carbon were analyzed. Generally, fine fractions (silt and clay) were predominant grain-size of the sediment ranging 21–35,8 % and 17,6–65,6 %, respectively, while total organic carbon (TOC) ranged from 0,30–1,49 %. Concentrations of p’,p’-DDT varied from 0,621–1,187ppb, concentrations of p’,p’-DDD ranged from 0,176–2,153 ppb and concentrations of p’,p’-DDE were from 0.181–2,254 ppb. The occurrence of total DDT (ΣDDT+DDD+DDE) tended to correlated positively to the fine fraction indicating as transport agent. DDD and DDE as DDT metabolites were formed by biological and chemical processes within predominantly aerobic condition. Keywords: pesticide, DDT, DDD, DDE, sediment, transport agent, Citarum, Jakarta Bay